Metabolomic and Transcriptomic Analyses Reveal That a MADS-Box Transcription Factor TDR4 Regulates Tomato Fruit Quality - Zhao, Xiaodan; Yuan, Xinyu; Chen, Sha; Fu, Da-Qi; Jiang, Cai-Zhong (Frontiers in Plant Science, 2019)
Tomato fruit ripening is a complex process, which determines the formation of fruit quality. Many factors affect fruit ripening, including environmental conditions and genetic factors. Transcription factors (TFs) play key roles in regulating fruit ripening and quality formation. Current studies have found that the TDR4 gene is an important TF for tomato fruit ripening, but its effects on fruit metabolism and quality are less well studied. In this study, suppression of TDR4 gene expression obtained through virus-induced gene silencing (VIGS) technology resulted in an orange pericarp phenotype. Transcriptomic analysis of TDR4-silenced fruit showed changes in the expression of genes involved in various metabolic pathways, including amino acid and flavonoid biosynthesis pathways. Metabolomic analysis showed that levels of several amino acids including phenylalanine and tyrosine, and organic acids were reduced in TDR4-silenced fruit, while α-tomatine accumulated in TDR4-silenced fruit. Taken together, our RNA-seq and metabolomics analyses of TDR4-silenced fruit showed that TDR4 is involved in ripening and nutrient synthesis in tomato fruit, and is therefore an important regulator of fruit quality.